Characterizing patient attitudes and beliefs towards testosterone therapy in Veterans Affairs: A qualitative study. (January 2023) - Engle, Ryann L.; Bokhour, Barbara G.; Rose, Adam J.; Reisman, Joel I.; Jasuja, Guneet K.
Abstract: Objective: We examined patient attitudes and beliefs and provider perspectives on patients' attitudes and beliefs towards testosterone therapy in Veterans Affairs (VA). Methods: We used a thematic analysis approach to understand variation in patient attitudes and beliefs towards testosterone at six VA sites with high and low levels of testosterone prescribing in VA. Semi-structured phone interviews with 18 patients and 22 providers at these sites were transcribed and coded using a priori theoretical constructs and emergent themes. A cross-case matrix of coded data was used to evaluate themes related to patient-level factors. Results: Patients' beliefs toward testosterone did not differ across sites. Patients, not providers, generally initiated conversations about testosterone. We identified five key domains related to patient beliefs and provider perceived patient beliefs towards testosterone: reasons for initiating testosterone, patient information sources and expectations about testosterone, receptivity towards discontinuation of testosterone, patient/provider engagement in information sharing, and self-advocacy by the patients in decision-making. Conclusions: Patient factors play an important role in testosterone prescribing decisions. Practice implications: By considering these patient factors, providers can potentially help create a partnership with patients and foster shared decision-making for testosterone and other, similar medications. Highlights: Patients generally initiated conversations about testosterone with their providers. Patient interest in initiating and discontinuing testosterone varied by age. Patient/provider engagement in information sharing influenced testosterone use. Patients expressed a need to play an active role in testosterone decision-making. Providers should consider patient factors to create a partnership with patients.